Improvement of Quality And Storage Stability of Ginger (Zingiber Officinale Rosc.) Drink. - Rantawaty, Fadney (2004)
A study was conducted to determine the physico-chemical characteristics of fresh ginger (Zingiber officinale Rosc.). The fresh ginger of Gajah/Betul variety of commercial maturity was used. The parameters analysed were weight, length, diameter, pH, titratable acidity (TA), total soluble solids (TSS), moisture content and crude fibre. This study concentration of the amount of pungent compounds in ginger such as 6-gingerol, 8-gingerol and 10-gingerol was determine by high performance liquid chromatography (HPLC). The concentration of 6-gingerol, 8-gingerol and 10-gingerol was 0.48 mg/100g, 0.04 mg/100 g and 0.05 mg/100 g, respetively.